Chapter 9 Living on the edge - Bhana, Deevia (Taylor & Francis, 2025)
This book examines the complex relationships between young masculinities and sexual health within Southern Africa. It considers how socio-cultural and economic factors shape young men’s experiences of masculinity and the effects on relationship dynamics, gender norms and sexual health. Through thematic chapters covering love, pleasure, social norms, risk, and HIV, the book emphasises the global importance of engaging young men in fostering gender equity and promoting healthier sexual practices. Readers will benefit from a diverse range of methodologies and perspectives that highlight the plurality and fluidity of masculinities, challenging monolithic accounts of young men in the region whilst illustrating the global relevance of understanding local contexts in shaping masculinities. The book provides valuable insights for developing effective sexual health interventions that recognise and embrace 'other' masculinities. Sexual health approaches that resonate with the lived realities of young men can potentially enhance young men’s engagement and participation in promoting healthier relationships and practices. With important insights for theory, policy, and practice, this book will be of interest to researchers across the fields of critical masculinity studies, sexual and reproductive health, gender studies and African studies, as well as policymakers, development practitioners, and activists.